A84 THE IMPACT OF GASTROINTESTINAL FOLLOW UP CARE ON HEALTHCARE UTILIZATION IN PATIENTS WITH EOSINOPHILIC ESOPHAGITIS (EOE). (4th March 2021) - Alazemi, K; Alkhattabi, M; Gregor, J C
Abstract: Background: EoE is an increasingly recognized gastrointestinal condition that causes significant morbidity ranging from dietary limitations to food impactions requiring emergency room visits. There are a variety of dietary, pharmacologic and endoscopic treatments available but most are more practically guided by a subspecialist familiar and experienced with the condition. There is a perception among some physicians that follow up is sporadic and may be related at least in part to patient compliance Aims: To assess patients with EoE utilization of health care in LHSC Methods: We used a retrospective cohort of patients diagnosed with EoE between July 2011 and June 2014 who met the traditional diagnostic criteria. As part of a quality improvement initiative, local follow up over the ensuing 5–7 years was tracked. The impact of follow up on subsequent healthcare utilization was analyzed. Results: 123 patients with biopsy confirmed EoE were analyzed. Follow up appointments were made for 114/123 (92%) patients. 55/123 (45%) had repeat elective endoscopy booked. Only 10/114 (8.7%) of initial appointments went unattended but 15/55 (27.2%) of the patients offered ongoing follow up failed to attend. There were no complications (ie. perforation or bleeding) attributable to any of the procedures. 5/123 (4%) patients required repeat emergency room endoscopy for food impaction. Two patients required this on multiple occasions. 4/5 patients requiring repeat emergency room endoscopy for food impaction had received some sort of follow up, although 4/5 of these had at least one missed appointment. 2/5 patients having emergency room endoscopy required overnight admission. There were no perforations in the cohort. Conclusions: Patients with a confirmed diagnosis of EoE do have a risk of requiring subsequent emergency endoscopy for food impaction although it is not clear that scheduled follow up significantly reduces that risk. Contrary to the perception of some physicians, patients with EoE are very likely to attend their first follow up visit although the attrition rate for subsequent scheduled visits is not insignificant. Funding Agencies: None